Porch, Port House - Ghosh, Ayan (2023)
A triple-arched projecting porch at Port House (Old Bombay Port Trust building). The semi-circular arches have projecting imposts and prominent keystones, the central arch being wider than the ones on the sides. The use of gray ashlar masonry blocks and brown sandstone accents provide strong color contrast.